INTERIORS OF RURAL SCHOOLS IN UKRAINE IN THE LATE XIX – BEGINNING OF XX CENTURY - ВЕРЕС, М. К. (Art and Design, 2022)
Purpose: to identify and analyze the artistic design of the interiors of rural schools in Ukraine in the late XIX – early XX century. Methodology. The research is based on the literary-analytical review of scientific works concerning the researched period and the analysis of the artistic decision of historical interiors of rural schools which have remained in museums of Ukraine and Europe (on an example of Poland). Results. With the beginning of the development of school construction in the late XIX – early XX centuries. in Ukraine, new types of public buildings were formed – folk rural schools. Which in this period significantly influenced the increase in education in rural areas and had the characteristics of folk style. Prominent architects were engaged in the design of schools, one of such architects in Ukraine was O. Slastyon, who in the early twentieth century. developed a number of school building projects for the Lokhvytsia zemstvo. At the same time, in Poland, architects Karol Siciński and Zdzisław Mączeński designed small schools, which eventually became typical of rural areas. School premises designed in rural areas in the late XIX – early XX centuries often had one – or two – three – four classes, as they were designed for a small community. However, the most common type, both in Ukraine and in European countries, were one- and two-class school buildings. The study analyzes the interiors of rural schools in Ukraine in the late XIX – early XX century in comparison with European examples of interiors of similar types of schools and identified the main elements of artistic design of school spaces that influenced modern interior design of schools in rural areas. Scientific novelty. The article analyzes and identifies the main trends in the artistic design of the interiors of rural schools in Ukraine in the late XIX – early XX century. For the first time, artistic solutions for the interiors of school buildings in rural areas of this period were considered, and similarities and differences between the artistic solutions for school interiors in Ukraine and European countries (on the example of rural schools in Poland) were revealed. Practical significance. The obtained results of the research can be used as historical theoretical materials of educational design in rural areas, as well as as a factual basis, which is a kind of continuation of the topics related to the study of domestic school spaces.